Akibat Hukum Putusan KPPU Nomor 05/KPPU-M/2022 atas Keterlambatan Pengambilalihan Saham - Arya Putra rizal; Dimas Hikari (Komisi Pengawas Persaingan Usaha, 2022)
Legal effect of the KPPU's Decision in the case of alleged delay in the acquisition of shares of PT. Nabati Agro Subur by Lestari Gemilang Intisawit (Number: 05/KPPU-M/2022) aims to objectively see whether the decision of the Commission Council in the case of unfair business competition is in accordance with the rule of law through Law Number 5 of 1999 concerning Monopolistic Practices and Competition unhealthy business and sanctions in the form of fines for business actors who have failed to notify them of the notification of share takeover. In this examination of the decision as an input for law enforcement against unfair business competition violations that result in losses for other business actors in doing business in a healthy manner. This research uses a doctrinal research method with a conceptual approach and laws and regulations. Through this paper it can be concluded that Decision Number 05/KPPU-M/2022 explains that PT. Gemilang Lestari Intisawit as a Subsidiary that acquired PT. Nabati Agro Subur is obliged to notify the KPPU of the takeover of shares. PT.GLI as a subsidiary of PT. Bumitama (legal entity) and after investigating that the acquisition resulted in an excess of the asset value and sales value of the parent company. Decision Number 05/KPPU-M/2022 has not provided the maximum penalty and there is a visible disparity between the reported actions that harm other business actors and the fine that is imposed only 1 trillion rupiah